Maternal effector T cells within decidua: The adaptive immune response to pregnancy?. (December 2017) - Lissauer, D.; Kilby, M.D.; Moss, P.
Abstract: In human pregnancy the maternal immune system plays a critical role in the regulation of many aspects of human reproduction including implantation, placentation and defence against infection. Interest has been focussed on the role of uterine natural killer cells (uNK) in the maternal decidua whereas effector CD4+ and CD8+ T cells have received much less attention despite the observation that they represent a major proportion of decidual leucocytes in the latter phase of pregnancy. A range of recent studies have demonstrated that human decidual T cells are highly differentiated, express a range of cytokines and cytotoxic markers, and demonstrate a unique transcriptional profile characterized by high level expression of genes involved in interferon-signalling. Moreover, subpopulations of effector T cells demonstrate specificity for fetal tissue and are regulated through expression of inhibitory checkpoint proteins and T regulatory cells. Nevertheless, many questions remain to be answered, such as the potential role of maternal effector T cells in either supporting successful pregnancy or potentially clearing fetal cells that have entered the maternal circulation. In addition, there is an increasing interest in the role of maternal effector T cells in the pathogenesis of disorders such as chronic villitis miscarriage, stillbirth, fetal growth restriction and pre-eclampsia. Current debates in relation to these questions will be discussed within this review. Highlights: CD45RO+ effector cells comprise the majority of T cells in decidua and are more differentiated than in blood. Human effector T cells express CXCR3 which may guide cells to decidua. These cells include populations that can produce IFNγ or Il-4. Microarray shows that decidual T cells demonstrate a transcriptional response to interferon signalling. T cells proliferate to cord blood indicating a response to fetal antigen and this increases after removing T regulatory cells.